Career choices of Rhodes University academics : internal and external influences on the decision making process - Rippon, Tamsyn (Rhodes University, Faculty of Humanities, Department of Psychology, 2014)
The career choice process, which emphasises the term 'choice', is one which is characterised by an ever changing multi-layered progression (Ozbilgin, Kusku & Erdogmus, 2004). This is due to the choice being a result of the on-going interaction between an individual and their social and organisational contexts. It is then safe to assume that this career decision making process involves an awareness of an individual's surrounding environment and an ability to acknowledge and understand what they regard as being important to them. In support of this understanding, this research project seeks to draw attention to the career influences of a specific group of professionals rather than researching career choices across a range of professionals within different contexts in efforts to broadly predict career choice behaviour. This study rather focuses on the factors that actively influenced the career choices of ten Rhodes University Academics across a range of disciplines and faculties and their individual career decision making processes. In drawing on "mainstream and heterodox" (Ozbilgin et al., 2004, p. 2) literature, this research aims to apply existing notions presented by past researchers to South African academics, now residing and working at Rhodes University, which is located in the small town of Grahamstown, Eastern Cape. The methods of qualitative inductive research are discussed and the results are explored within the settings and contexts unique to each individual who has been drawn to the specific University context. The purpose of the study is to therefore adopt an inductive thematic analysis approach in seeking to examine the internal and external factors that served to influence the sample of academics into their chosen discipline, their decision to become and academic and their employer of choice, in light of the increasing pressure on higher education institutions to contribute to social and economic transformation within the South Africa (Tettey, 2006).
Keywords: Rhodes University -- Vocational guidance; Vocational guidance; Career development -- South Africa -- Grahamstown; College teachers -- Job satisfaction -- South Africa -- Grahamstown; Universities and colleges -- Faculty; Qualitative research